Cigarette Smoke Promotes Interleukin-8 Production in Alveolar Macrophages Through the Reactive Oxygen Species/Stromal Interaction Molecule 1/Ca2+ Axis - Zhu, Xianying; Zhan, Yuan; Gu, Yiya; Huang, Qian; Wang, Ting; Deng, Zhesong; Xie, Jungang (Frontiers in Physiology, 2021)
Chronic obstructive pulmonary disease (COPD), primarily attributed to cigarette smoke (CS), is characterized by multiple pathophysiological changes, including oxidative stress and inflammation. Stromal interaction molecule 1 (STIM1) is a Ca2+ sensor that regulates Ca2+ entry in different types of cells. The present study aimed to explore the relationship between CS-induced oxidative stress and inflammation, as well as the functional role of STIM1 thereinto. Our results showed that the reactive oxygen species (ROS)/STIM1/Ca2+ axis played a critical role in CS-induced secretion of interleukin (IL)-8 in human alveolar macrophages. Specifically, smokers with COPD (SC) showed higher levels of ROS in the lung tissues compared with healthy non-smokers (HN). STIM1 was upregulated in the lung tissues of COPD patients. The expression of STIM1 was positively associated with ROS levels and negatively correlated with pulmonary function. The expression of STIM1 was also increased in the bronchoalveolar lavage fluid (BALF) macrophages of COPD patients and PMA-differentiated THP-1 macrophages stimulated by cigarette smoke extract (CSE). Additionally, CSE-induced upregulation of STIM1 in PMA-differentiated THP-1 macrophages was inhibited by pretreatment with N-acetylcysteine (NAC), a ROS scavenger. Transfection with small interfering RNA (siRNA) targeting STIM1 and pretreatment with NAC alleviated CSE-induced increase in intracellular Ca2+ levels and IL-8 expression. Furthermore, pretreatment with SKF-96365 and 2-APB, the inhibitors of Ca2+ influx, suppressed CSE-induced secretion of IL-8. In conclusion, our study demonstrates that CSE-induced ROS production may increase the expression of STIM1 in macrophages, which further promotes the release of IL-8 by regulating Ca2+ entry. These data suggest that STIM1 may play a crucial role in CSE-induced ROS production and inflammation, and participate in the pathogenesis of COPD.